M. Heidegger’s philosophy mirrored in sociology of knowledge of P. Bourdieu and R. Collins - Andriy Karpenko (Cхід, 2013)
Heidegger proved to be one of the key thinkers of the last century. His philosophical legacy accompanied by affluent body of critical literature disclose the horizon for any local philosophical community, e. g. the Ukrainian one, to obtain its own language and problematic. To work out a appropriate receptive disposition towards Heidegger’s thought, we have to generalize the logics of some constituted histories of reading Heidegger in Continental, Anglo-Saxon, and Russian intellectual fields. Contemporary historico-philosophical discourse dominated by receptive disposition of history of ideas omits social references of philosophical texts. This is symptomatic for ontological, existential, and lingual focuses on Heidegger, so characteristic for Ukrainian studies. We try to work out the interpretative disposition of situational analysis of Heidegger’s discourse on the methodological and conceptual basis provided by P. Bourdieu and R. Collins’s sociological views on Heidegger. Our goal here is to find a possibility to appropriate certain elements from sociology of knowledge to the apparatus of historico-philosophical analysis, although sociology of knowledge is suspected to be more valuable in explaining biasis than in accounting for correct opinions and adequate interpretations. This controversy between sociological and philosophical fields made us consider the critical reception of P. Bourdieu’s issues. What is really relevant to the tasks of historical and logical reconstructions of Heidegger’s thought, its contexts and evolution is Bourdieu’s claim to consider its polyphonic nature, its stylistics evolving from pragmatic force of Sein und Zeit to prophecies of the poetic thinking to come in the history of Being. We argue that such concepts of sociology of knowledge as structural homology, intellectual field, and symbolic capital can substantially enforce and enrich historico-philosophical studies, being framed in the disposition of situational analysis of philosophical texts.